Etiology of Bloody Diarrhea among Children Admitted to Maternity and Children ’ s Hospital-Erbil - Rabatti, Abbass A.; Rasheed, Nazdar Ezzaddin (AL-Kindy College Medical Journal, 2008)
Background: Bloody diarrhea plays a major role in morbidity and mortality especially in developing countries, it is usually a sign of invasive enteric infection, there is a thought that amoebic dysentery is more common than bacillary dysentery in Iraq, and from 1989 to 1997 amoebic dysentery increase from 20000to 550000 patients. Objectives: This study aims to: 1. Outline the incidence of various infectious causes of bloody diarrhea in Erbil district. 2. Assess the effect of multiple factors like age, sex, source of water supply, etc... On the incidence of amebic and bacillary dysentery. 3. To provide baseline data for making strategic plan to reduce the diarrhoeal mortality and morbidity. Methods: A prospective case- series study was conducted on 116 infants and children aged 2 month – 12 years admitted to hospital complaining of bloody diarrhea. Information was taken from their mothers regarding (age, sex, geographical area, feeding pattern and source of water supply) , their stool have been examined for the presence of RBC, leukocyte, parasitic cyst and trophozoit, however blood examination was conducted for the presence of band. Results: The results reveal 77.5% of patients were in the younger age group (<2 year). Entamoeba histolytica was the most common enteropathogen isolated in 60.3% of patients, other enteropathogens identified were Shigella 3.5%, E.coli2.6%, Salmonella2.6%, mixed infection were reported in 1.72%, 28.5%of patients have non isolated pathogen. On the other hand, source of water supply and type of feeding have significant effect on incidence of enteropathogens. The presence of fever, vomiting, convulsion and band in peripheral blood mostly indicates bacterial etiology. Conclusion: Entamoeba histolytica was the commonest enteropathogen isolated; the incidence of bloody diarrhea was more in younger age group. There was significant effect of source of water supply on the incidence of bloody diarrhea with most enteropathogen isolated from patients who have well water supply. Breastfeeding was protective against enteropathogen especially bacterial agents in infants under 6 month of age. Presence of band in the peripheral blood indicates most probably bacterial agents